2014
DOI: 10.1089/end.2014.0094
|View full text |Cite
|
Sign up to set email alerts
|

Performing in the Surgical Amphitheater of Today: Perception of Urologists Conducting Live Case Demonstrations

Abstract: LCDs are perceived to be an effective mode of education by performers and moderators of LCDs. Standard guidelines and policies are needed, however, for the selection of patient, surgeon and team, equipment, and facility. Studies are needed to evaluate the impact of this education process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…These concerns are in concordance with the outcomes of other survey studies [ 7 , 9 12 ]. In the study by Elsamra et al, 22% of the survey respondents had doubts about the ethical value of LSD and 41% of the respondents would not participate as a patient themselves [ 9 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These concerns are in concordance with the outcomes of other survey studies [ 7 , 9 12 ]. In the study by Elsamra et al, 22% of the survey respondents had doubts about the ethical value of LSD and 41% of the respondents would not participate as a patient themselves [ 9 ].…”
Section: Discussionsupporting
confidence: 91%
“…The items addressed in the survey were based on the literature and on input from the organizers, who coordinated the live and semi-live surgeries [ 7 , 9 12 ]. A committee of ten test participants reviewed the survey questions in several rounds to ensure the comprehensibility.…”
Section: Methodsmentioning
confidence: 99%
“…The benefit of live surgery events for surgical training has been repeatedly and critically discussed [21,23,36]. However, we observed a high degree of approval for this training concept.…”
Section: Discussionmentioning
confidence: 78%
“…A large number of surgeons are introduced to new surgical techniques and the relevant clinical anatomy is demonstrated on a single patient [19,21]. Furthermore, live surgery events offer the opportunity to learn from experts as a role model in real life, as well as handle surgical complications and manage difficult cases appropriately [22,23]. Such events are especially attractive in minimally invasive surgery because the perspective of the operating surgeon is directly transmitted to the attendees in the auditorium, who then participate virtually in the operation [20].…”
Section: Introductionmentioning
confidence: 99%
“…We have used live case demonstrations (LCDs) to teach others minimally invasive surgery. Salami et al [6] have shown that LCDs are perceived to be an effective mode of education by performers and moderators.…”
Section: Discussionmentioning
confidence: 99%